Oregano essential oil and its main components Thymol and Carvacrol as alternatives to control citrus canker - Zamuner, Caio Felipe Cavicchia; Marin, Vítor Rodrigues; Dilarri, Guilherme; Hypolito, Giovane Boerner; Sass, Daiane Cristina; Ferreira, Henrique (Frontiers in Agronomy, 2023)
Plant Essential Oils and their constituents are well-known for their properties as antimicrobial agents and are labeled as Generally Recognized as Safe (GRAS), prompting studies around their usage in the control of food-borne microorganisms and phytopathogens. In this study, we evaluated Oregano Essential Oil (OEO), Thymol (THY) and Carvacrol (CAR) for the control of Xanthomonas citri subsp. citri (X. citri). In vitro antibacterial assays revealed that CAR and THY inhibit X. citri growth at concentrations (100 ug.mL-1 and 114 ug.mL-1) lower than OEO (136 ug.mL-1). Bactericidal effects were observed at 400 ug.mL-1 for OEO and 200 ug.mL-1 for CAR and THY. Investigating potential cellular targets for the compounds showed that after 30 minutes of exposure up to 84% of the cells had their membranes disrupted, prompting the membrane as the primary target. Phytotoxicity evaluations using Lactuca sativa and Solanum lycopersicum seeds showed an acute toxic effect in all treatments above 200 µg.mL-1, except for OEO and THY in S. lycopersicum at lower concentrations. Regarding their protective effect on citrus leaves, CAR showed no effect (0.39 lesions per cm2) when compared to the controls. OEO and THY were able to significantly reduce citrus canker symptoms (0.18 and 0.11 lesions per cm2, respectively). In addition, no toxic effects were observed on citrus leaves. THY inhibits X. citri growth and the development of citrus canker lesions. These results prompt THY as a viable alternative to be used in citrus canker management.